Construct and concurrent validity of the short- and long-form versions of the trait emotional intelligence questionnaire. (October 2016) - Laborde, Sylvain; Allen, Mark S.; Guillén, Félix
Abstract: This study tested the concurrent validity of the short-form version of the trait emotional intelligence questionnaire (TEIQue-SF) against the long-form version (TEIQue-LF), and the construct validity of each questionnaire. In total, 1889 Spanish adults (935 women, 954 men; mean age = 21.56 years, age range = 18–37 years) completed the TEIQue-SF and TEIQue-LF, the order of which was counterbalanced across participants. Confirmatory factor analysis supported the 4-factor structure of both the short-form and long-form versions, with marginally stronger factor loadings observed for the long-form. Bivariate correlations demonstrated a high degree of similarity in scoring on the TEIQue-SF and TEIQue-LF for each subscales and the global trait emotional intelligence (EI): well-being ( r = 0.76), self-control ( r = 0.69), emotionality ( r = 0.78), sociability ( r = 0.71), and global trait EI ( r = 0.83). Overall, findings indicate that the TEIQue-SF is a viable alternative to the TEIQue-LF for research in time-restricted conditions where the completion of long questionnaires might be unfeasible. Highlights: Trait emotional intelligence questionnaire (TEIQue) Comparison of short-form (TEIQue-SF) and long-form (TEIQue-LF) versions Strong correlations for the factors and global score between both versions